(2x+2)(x+1)=1

Simple and best practice solution for (2x+2)(x+1)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+2)(x+1)=1 equation:


Simplifying
(2x + 2)(x + 1) = 1

Reorder the terms:
(2 + 2x)(x + 1) = 1

Reorder the terms:
(2 + 2x)(1 + x) = 1

Multiply (2 + 2x) * (1 + x)
(2(1 + x) + 2x * (1 + x)) = 1
((1 * 2 + x * 2) + 2x * (1 + x)) = 1
((2 + 2x) + 2x * (1 + x)) = 1
(2 + 2x + (1 * 2x + x * 2x)) = 1
(2 + 2x + (2x + 2x2)) = 1

Combine like terms: 2x + 2x = 4x
(2 + 4x + 2x2) = 1

Solving
2 + 4x + 2x2 = 1

Solving for variable 'x'.

Reorder the terms:
2 + -1 + 4x + 2x2 = 1 + -1

Combine like terms: 2 + -1 = 1
1 + 4x + 2x2 = 1 + -1

Combine like terms: 1 + -1 = 0
1 + 4x + 2x2 = 0

Begin completing the square.  Divide all terms by
2 the coefficient of the squared term: 

Divide each side by '2'.
0.5 + 2x + x2 = 0

Move the constant term to the right:

Add '-0.5' to each side of the equation.
0.5 + 2x + -0.5 + x2 = 0 + -0.5

Reorder the terms:
0.5 + -0.5 + 2x + x2 = 0 + -0.5

Combine like terms: 0.5 + -0.5 = 0.0
0.0 + 2x + x2 = 0 + -0.5
2x + x2 = 0 + -0.5

Combine like terms: 0 + -0.5 = -0.5
2x + x2 = -0.5

The x term is 2x.  Take half its coefficient (1).
Square it (1) and add it to both sides.

Add '1' to each side of the equation.
2x + 1 + x2 = -0.5 + 1

Reorder the terms:
1 + 2x + x2 = -0.5 + 1

Combine like terms: -0.5 + 1 = 0.5
1 + 2x + x2 = 0.5

Factor a perfect square on the left side:
(x + 1)(x + 1) = 0.5

Calculate the square root of the right side: 0.707106781

Break this problem into two subproblems by setting 
(x + 1) equal to 0.707106781 and -0.707106781.

Subproblem 1

x + 1 = 0.707106781 Simplifying x + 1 = 0.707106781 Reorder the terms: 1 + x = 0.707106781 Solving 1 + x = 0.707106781 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0.707106781 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0.707106781 + -1 x = 0.707106781 + -1 Combine like terms: 0.707106781 + -1 = -0.292893219 x = -0.292893219 Simplifying x = -0.292893219

Subproblem 2

x + 1 = -0.707106781 Simplifying x + 1 = -0.707106781 Reorder the terms: 1 + x = -0.707106781 Solving 1 + x = -0.707106781 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = -0.707106781 + -1 Combine like terms: 1 + -1 = 0 0 + x = -0.707106781 + -1 x = -0.707106781 + -1 Combine like terms: -0.707106781 + -1 = -1.707106781 x = -1.707106781 Simplifying x = -1.707106781

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.292893219, -1.707106781}

See similar equations:

| z^2-4iz-29=0 | | p(-2)=x^2-2x | | 2x^-6x/5=6 | | g(-1)=2x^2+5 | | Sin(2*x-pi/2) | | -x=1-x | | 2x(x-3/5)-6 | | 9q-3p+7= | | 3/2*=1/8 | | 5x+9=3x+8 | | 5x+9=3y+8 | | 3y+8=5x+9 | | 7=11 | | y^2dx+(xy+tanxy)dy=0 | | 2x=8/2 | | f(x+2)=3x-4 | | (x-120)*1.8+60=90 | | 1/5x=70 | | 5g-1=3g+4 | | sqrt(17-y)+sqrty(y)=5 | | 3x=5(7) | | 100=x/2*100 | | X=100-(x*15/100) | | 3x+9x-5x= | | -0.12p=2.56+5p | | X=2*10 | | (t)(sqrt(4-t))=0 | | 10n+5=5 | | y=8x^2-6x-14 | | 4-4*5-3= | | -19/5*-4 | | 19/5*-4 |

Equations solver categories